1979
DOI: 10.1104/pp.64.5.852
|View full text |Cite
|
Sign up to set email alerts
|

Relative Sensitivity of Photosynthetic Assimilation and Translocation of 14Carbon to Water Stress

Abstract: The relationship between photosynthesis and translocation rate changes as affected by water stress intensity and stage of plant development was evaluated in cotton and sorghum, representing a C3 and a C4 photosynthetic type, respectively. Photosynthetic rates were reduced as midday leaf water potentials declined from -14 to -27 bars in both species. Sorghum maintained higher photosynthesis and translocation rates compared to cotton at comparable leaf water potentials; however, the rate of change per bar declin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 15 publications
6
21
1
Order By: Relevance
“…High concentrations of solute in the phloem also allow the sieve elements to maintain turgor, and to continue to function, when the plant is under severe water stress (Sung and Krieg, 1979;Smith and Milburn, 1980). However, there is reason to doubt that active loading is needed to establish and maintain this pressure since many plants with the longest transport distances function without it.…”
Section: Resultsmentioning
confidence: 99%
“…High concentrations of solute in the phloem also allow the sieve elements to maintain turgor, and to continue to function, when the plant is under severe water stress (Sung and Krieg, 1979;Smith and Milburn, 1980). However, there is reason to doubt that active loading is needed to establish and maintain this pressure since many plants with the longest transport distances function without it.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the best temperature regime for reproductive structure retention in cotton was day/night temperatures of 32/22 ºC. Maximum net photosynthesis in cotton leaves occurs around 32 o C (Sung and Krieg, 1979), but respiration increases almost linearly with higher temperatures resulting in less carbohydrates available for fruit growth at high temperatures, fruit shedding and decreased yields; usually a good vegetative/reproductive balance in cotton is observed when the average temperature is around 25 o C (Pettigrew, 2008). The competition between vegetative and reproductive growth for photoassimilates is decreased by mepiquat chloride use (Gwathmey and Clement, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Such a drastic change might be induced under much severer or longer drought conditions than ours, because more than 80% of the maximum contents of the major photosynthetic pigments maintained in wheat leaves under drought (Table 2). In young leaves, expansion growth is more sensitive to water-deficit, than photosynthesis (Boyer 1970) or translocation (Sung and Krieg 1979). Therefore, we concluded that the growth rate might be determined by more watersensitive activities other than photosynthesis or pigment biosynthesis.…”
Section: Impacts Of Drought Stress On Growth and Physiological Paramementioning
confidence: 96%